Development of Students’ worksheets Oriented Socio-Scientific Issues on Salt Hydrolysis Topic to Enhance Problem-Solving Skills and Learning Motivation of High School Students - Azizah, Fidasari Nur; Atun, Sri (Jurnal Pendidikan MIPA, 2025)
This study aims to (1) describe the characteristics of students’ worksheets oriented towards Socio-Scientific Issues (SSI), (2) test their feasibility, (3) analyze the differences in problem-solving skills and learning motivation among students who use SSI-oriented students’ worksheets and those who do not, and (4) determine the effectiveness of SSI-oriented students’ worksheets to enhance problem-solving skills and learning motivation. The research method used Thiagarajan's 4D model (Define, Design, Develop, Disseminate) with a quasi-experimental pretest-posttest control group design and a sample size of N=112. Data was analyzed using MANOVA and Partial Eta Square. The results showed that the SSI-oriented students’ worksheets : (1) consists of four structured activities (stimulation, problem identification, data collection, data processing, proof, and conclusion) designed to enhance problem-solving skills and learning motivation, (2) was highly feasible based on expert validation of quality by teachers and readability testing by students, (3) MANOVA analysis (Hotelling’s Trace) revealed significant differences (p < 0.05) in problem-solving skills and learning motivation between the experimental class (using SSI-oriented students’ worksheets) and the control class, both simultaneously and partially. (4) SSI-oriented students’ worksheets contributed effectively by 12.5% to the simultaneous improvement of problem-solving skills and learning motivation, with a moderate effect category, which indicates a significant influence. Partially, the contribution to problem-solving skills reached 9.1% and learning motivation 4.8%. Although the contribution to learning motivation is relatively lower, the overall use of this student’s worksheet still has a significant positive impact on the chemistry learning process. The study statistically proves that these SSI-oriented students’ worksheets are a practical and significant intervention to improve students' problem-solving skills and learning motivation in chemistry lessons, providing a bridge between theoretical concepts and real-world issues. However, its effective contribution is classified as moderate.      Keywords: learning motivation, problem-solving skills, salt hydrolysis, socio-scientific issues, students’ worksheets.